Subarachnoid Hematoma of the Craniocervical Junction and Upper Cervical Spine After Traumatic Cerebral Contusion: Case Report - Di Rienzo, Alessandro (Neurol Med Chir (Tokyo), 2013)
Spinal subarachnoid hematoma (SSH) is a rare condition, more commonly occurring after lumbar puncture for diagnostic or anesthesiological procedures. It has also been observed after traumatic events, in patients under anticoagulation therapy or in case of arteriovenous malformation rupture. In a very small number of cases no causative agent can be identified and a diagnosis of spontaneous SSH is established. The lumbar and thoracic spine are the most frequently involved segments and only seven cases of cervical spine SSH have been described until now. Differential diagnosis between subdural and subarachnoid hematoma is complex because the common neuroradiological investigations, including a magnetic resonance imaging (MRI), are not enough sensitive to exactly define clot location. Actually, confirmation of the subarachnoid location of bleeding is obtained at surgery, which is necessary to resolve the fast and sometimes dramatic evolution of clinical symptoms. Nonetheless, there are occasional reports on successful conservative treatment of these lesions. We present a peculiar case of subarachnoid hematoma of the craniocervical junction, developing after the rupture of a right temporal lobe contusion within the adjacent arachnoidal spaces and the following clot migration along the right lateral aspect of the foramen magnum and the upper cervical spine, causing severe neurological impairment. After surgical removal of the hematoma, significant symptom improvement was observed.